THE JOB STRESS, WORKLOAD, EXERCISE HABITS AND METABOLIC SYNDROME IN ACADEMIC PERSONNEL AT AIRLANGGA UNIVERSITY - Ratih Damayanti; Ratnaningtyas Wahyu Kusuma Wardhani; Berliana Devianti Putri; Indah Lutfiya (Malaysian Journal of Public Health Medicine, 2020)
Every human individual must have experienced stress. Especially in situations or conditions with high stressors, one of which is the work factor. Job stress can have an effect on the occurrence of health problems, one of them is metabolic syndrome. The purpose of this study was to analyze the relationship between work stress, workload, exercise habits and metabolic syndrome in employees in Offices (case study at Airlangga University). This study was an observational analytic study with a cross-sectional research design. The population of this research is all education staff / academic staff, namely in the finance, human resources, infrastructure, academic, student, quality assurance, information system units, dean secretariat, laboratory staff and receptionist at Airlangga University. The sample size involved in this study was 70 people. A significant factor influencing the occurrence of metabolic syndrome is work stress and exercise habits. Meanwhile, the factors that influence the occurrence of work stress are age and workload. Each age increases by 1 year, the risk of work stress increases 1,126 times. Increasing the level of work stress increases the risk of developing metabolic syndrome by 1,146 times. The less regular exercise is, the risk of metabolic syndrome increases by 58 times. One of the efforts to solve the problem of metabolic syndrome are by exercising regularly and managing stress well. In addition, given the opportunity to exercise in between work and the presence of sports facilities in the work area can help reduce the risk of getting metabolic syndrome and work stress.